Peran Diplomasi Budaya Dalam Menanggapi Tantangan Globalisasi Dan Perbedaan Budaya Untuk Meningkatkan Pertahanan Nasional Di Indonesia - Alisya Rahma Saebani; Irwan Triadi (Lembaga Pengembangan Kinerja Dosen, 2023)
In facing the complexity of globalization, Indonesia as a country rich in cultural diversity and traditions faces challenges in maintaining its national identity. Cultural diplomacy is identified as a crucial instrument in enhancing national resilience through mutual understanding, respect for diversity, and strengthening national identity. This article discusses the diplomatic role of the Ministry of Foreign Affairs in managing cultural differences and describes how cultural diplomacy is a vital element in national defense, in accordance with Law Number 3 of 2002 concerning national defense. The case study of cooperation between Indonesia and South Korea through the Hallyu phenomenon illustrates the impact of cultural diplomacy on the economy, politics and society. This research uses normative juridical research methods or also called library research. The data collection is done secondarily, involving primary, secondary, and tertiary legal materials, such as laws, books, journals, and related articles. The results show that in the midst of global cultural changes, cultural diplomacy is also faced with challenges, including multidimensional threats involving physical and non-physical aspects. Therefore, the integration of cultural diplomacy in national security policy is essential to maintain cultural diversity and national identity.